2012
DOI: 10.1016/j.jcps.2012.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Pleasure principles: A review of research on hedonic consumption

Abstract: 2016-12-23T18:52:10

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
329
1
20

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 510 publications
(396 citation statements)
references
References 240 publications
7
329
1
20
Order By: Relevance
“…These results fall in line with some past research presenting conservation volunteering travel as a primarily emotional hedonic experience (e.g., Alba and Williams 2013) or studies of propensity to engage in pro-environmental activities among visitors to wildlife areas (Lemelin et al 2008). In this, light conventional tourism stands for more traditional consumer values of material possessions or personal wealth (Fournier and Richins 1991) leading to convenience, variety, quality, or low price seeking behavior, while travel for conservation volunteering is associated with positive emotions and emotional desires.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These results fall in line with some past research presenting conservation volunteering travel as a primarily emotional hedonic experience (e.g., Alba and Williams 2013) or studies of propensity to engage in pro-environmental activities among visitors to wildlife areas (Lemelin et al 2008). In this, light conventional tourism stands for more traditional consumer values of material possessions or personal wealth (Fournier and Richins 1991) leading to convenience, variety, quality, or low price seeking behavior, while travel for conservation volunteering is associated with positive emotions and emotional desires.…”
Section: Discussionsupporting
confidence: 93%
“…In this, light conventional tourism stands for more traditional consumer values of material possessions or personal wealth (Fournier and Richins 1991) leading to convenience, variety, quality, or low price seeking behavior, while travel for conservation volunteering is associated with positive emotions and emotional desires. These positive emotional desires translate into a person's need for pleasurable and interesting experiences (Pearce 2009;Alba and Williams 2013;Malone et al 2014). Lemelin et al (2008) suggested that research has made a faulty assumption that visitors to wildlife areas share positive environmental ethics, biocentric values, and intrinsic motives (e.g., Acott et al 1998;Honey 1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of mechanics, such as the use of real names or publicizing rewards, should depend on the extent to which products are used to signal identity (Berger and Heath 2007). Aesthetics should be more important for hedonic than utilitarian products, although both types of products should benefit from enhanced aesthetics (Alba and Williams 2013). The importance of particular technology features, such as virtual reality, should also be more important for products that are highly experiential (Suh and Lee 2005).…”
Section: Product-related Moderatorsmentioning
confidence: 99%
“…As a final thought, Alba and Williams (2013) review the body of knowledge related to hedonic consumption and similarly conclude that the concepts of flow and flourishing associated with eudaimonia appear achievable, even without an abundance of positive emotion, when accomplishment is the dominant form of flourishing. That is, activities can be emotionally satisfying and more motivating than material gain if imbued with meaning and a sense of progress.…”
Section: Resultsmentioning
confidence: 99%